2021
DOI: 10.3390/nano11071808
|View full text |Cite
|
Sign up to set email alerts
|

Group Velocity Modulation and Light Field Focusing of the Edge States in Chirped Valley Graphene Plasmonic Metamaterials

Abstract: The valley degree of freedom, like the spin degree of freedom in spintronics, is regarded as a new information carrier, promoting the emerging valley photonics. Although there exist topologically protected valley edge states which are immune to optical backscattering caused by defects and sharp edges at the inverse valley Hall phase interfaces composed of ordinary optical dielectric materials, the dispersion and the frequency range of the edge states cannot be tuned once the geometrical parameters of the mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Moreover, Monfared et al have achieved the photoelectric switch operation by utilizing the unique optical properties of SPPs supported by graphene [30][31][32] Recently, Dehghan et al reported the graphene periodic lattice, which causes plasmonic modes to absorb a specific Terahertz frequency band and minimize transmission [33]. Graphene-supported SPPs have been recognized as a promising two-dimensional material for a wide range of applications such as transparent electronics, gate modulators, photocatalysts, and more [25,29,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Monfared et al have achieved the photoelectric switch operation by utilizing the unique optical properties of SPPs supported by graphene [30][31][32] Recently, Dehghan et al reported the graphene periodic lattice, which causes plasmonic modes to absorb a specific Terahertz frequency band and minimize transmission [33]. Graphene-supported SPPs have been recognized as a promising two-dimensional material for a wide range of applications such as transparent electronics, gate modulators, photocatalysts, and more [25,29,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue includes five articles [1][2][3][4][5] which present some of the challenges and opportunities in the field of plasmonics and nanophotonics.…”
mentioning
confidence: 99%
“…Zhuo et al [4] propose tunable valley graphene plasmonic metamaterials (VGPMs) for group velocity modulation and light field focusing of surface plasmon polariton waves. The authors further discuss a chirped VGPM waveguide composed of a supercell arrangement of VGPMs with a gradually increasing chemical potential difference.…”
mentioning
confidence: 99%